Acoustical and vibrational procedures for investigating the modal response of structures - Williams, P.G.(Paul Gareth), 1960- (1994)
Thesis (M.Eng.)--Memorial University of Newfoundland, 1994. Engineering and Applied Science Bibliography: leaves 163-167. The modal characteristics of structures are normally established experimentally through the use of accelerometers and force transducers to measure the frequency response under different excitation frequencies. Variations in the modal frequencies and the mode shapes can be determined for different structural modifications. Modal properties can also be determined through measurement of the acoustical properties of the structure, particularly in the quantity and direction of acoustic energy flow. Such measurements, because they are non-contacting, offer the advantage of eliminating modification of the modal response due to the mass of the accelerometers as well as ease of use where accelerometer attachment is difficult, for example, on fibre composite structures. Experiments were designed to investigate the ease and accuracy of such acoustic measurements by comparing results from the acoustic energy flow methods with more classical vibrational techniques. -- The structure was then modified through the introduction of a machined notch and the acoustic modal properties measured again for comparison. -- A method is presented for the use of acoustic energy flow mapping in the detection of structural defects which result in the modification of the modal frequencies and amplitudes.